2010
DOI: 10.1021/jf1013764
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects and the Mechanisms of Anti-inflammation of Ergostatrien-3β-ol from Antrodia camphorata Submerged Whole Broth in Mice

Abstract: Ergostatrien-3β-ol (ST1), an active and major ingredient from Antrodia camphorata (AC) submerged whole broth was evaluated for the analgesic and anti-inflammatory effects. Treatment of male imprinting control region (ICR) mice with ST1 (1, 5, and 10 mg/kg) significantly inhibited the numbers of acetic-acid-induced writhing response in 10 min. Also, our result showed that ST1 (10 mg/kg) significantly inhibited the formalin-induced pain in the late phase (p < 0.001). In the anti-inflammatory test, ST1 (10 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 29 publications
1
73
0
1
Order By: Relevance
“…In contrast, A. cinnamommea is an endemic mushroom that is restricted to the endemic aromatic tree Cinnamomum kanehirai Hayata in Taiwan. The economic value of A. cinnamommea is mainly due to its medicinal use (8)(9)(10)(11). According to Ortiz-Santana et al (3), A. cinnamomea (T. camphorates) belongs to a clade that includes Taiwanofungus, Dacryobolus, and other related genera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, A. cinnamommea is an endemic mushroom that is restricted to the endemic aromatic tree Cinnamomum kanehirai Hayata in Taiwan. The economic value of A. cinnamommea is mainly due to its medicinal use (8)(9)(10)(11). According to Ortiz-Santana et al (3), A. cinnamomea (T. camphorates) belongs to a clade that includes Taiwanofungus, Dacryobolus, and other related genera.…”
Section: Discussionmentioning
confidence: 99%
“…cinnamomea is rich in polysaccharides (4) and produces specific ergostane triterpenoids, including antcins C and K (5), zhankuic acids A, B, and C (6), and antrocamphin (7). A. cinnamomea has long been the most valued medicinal fungus in Taiwan, as a remedy for various diseases, including hypertension, abdominal pains, hepatitis B, and cancers (8)(9)(10)(11). Also, the extract of A. cinnamomea has long been used to ameliorate the effects of alcohol intoxication.…”
mentioning
confidence: 99%
“…Other reports showing the oxidative stress-related disease suppressive effect of antioxidants were col- and selectively extracted from these reports [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ( Table 2). Dataset 2 had 122 records in 17 reports and 6% missing values.…”
Section: Introductionmentioning
confidence: 99%
“…10) Our results showed that doi: 10.3769/radioisotopes.67. 43 2 1 Datasets Dataset 1 was selectively extracted from our reports over the past five years. They show the suppressive effects on the oxidative stress-related diseases induced by low-dose radiation [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Os neurônios do gânglios da raiz dorsal são considerados os principais alvos de ação da cisplatina, podendo causar danos no DNA nuclear e morte celular (Cavaletti et al, 1995;Carozzi et al, 2015) e (Huang et al, 2010). Embora o efeito da cisplatina em danos no DNA nuclear tenha sido amplamente investigado, sua interação com DNA mitocondrial foi apenas recentemente investigado (Podratz et al, 2011).…”
Section: Mecanismos De Ação Da Cisplatinaunclassified